2016
DOI: 10.1007/s10877-016-9839-3
|View full text |Cite
|
Sign up to set email alerts
|

The effects of anesthetic agents on pupillary function during general anesthesia using the automated infrared quantitative pupillometer

Abstract: Pupil reactivity can be used to evaluate central nervous system function and can be measured using a quantitative pupillometer. However, whether anesthetic agents affect the accuracy of the technique remains unclear. We examined the effects of anesthetic agents on pupillary reactivity. Thirty-five patients scheduled for breast or thyroid surgery were enrolled in the study. Patients were divided into four groups based on the technique used to maintain anesthesia: a sevoflurane-remifentanil (SEV/REM) group, a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 16 publications
3
40
2
Order By: Relevance
“…High-dose propofol [29] also may potentially reduce the NPi; however, the infusion dose of propofol was kept < 4 mg/kg in our study. It was shown by Delfino et al that infused propofol at 100 μg/kg/min (= 6 mg/kg/h) resulted in bispectral index (BIS) monitoring values of approximately 42 [30], and indeed, at this infusion rate, propofol has no effect on the NPi (while it significantly reduced pupil size and percentage constriction) [31]. Finally, it is worth noting that the NPi value is adjusted to individual resting pupil size [32].…”
Section: Discussionmentioning
confidence: 99%
“…High-dose propofol [29] also may potentially reduce the NPi; however, the infusion dose of propofol was kept < 4 mg/kg in our study. It was shown by Delfino et al that infused propofol at 100 μg/kg/min (= 6 mg/kg/h) resulted in bispectral index (BIS) monitoring values of approximately 42 [30], and indeed, at this infusion rate, propofol has no effect on the NPi (while it significantly reduced pupil size and percentage constriction) [31]. Finally, it is worth noting that the NPi value is adjusted to individual resting pupil size [32].…”
Section: Discussionmentioning
confidence: 99%
“…Second, concurrent use of drugs that could confound the evaluation of the PLR such as opioids, anticholinergics, or sedative agents was not evaluated. Although a previous study showed that the use of these medications within therapeutic doses does not signi cantly suppress the PLR [38], we cannot exclude the possibility that other medications such as propofol may have affected the PLR [39]. Third, we did not analyze confounders such as underlying pathology of the retina or optic nerve as well as the in uence of ambient lights on the PLR [40].…”
Section: Discussionmentioning
confidence: 99%
“…18,19 One recent study established that fentanyl decreased pupil size and altered pupil light reactivity but did not change the NPi. 18 Another study observed transient, symmetrical CV reductions in an outpatient population after administration of narcotics (oral or IV) and benzodiazepines.…”
Section: Discussionmentioning
confidence: 99%